Two new species of Micropterus (Centrarchidae) endemic to Atlantic Slope river drainages in Georgia, South Carolina and North Carolina, U.S.A. - Freeman, Byron J.; Scott, Mark C.; Petersen, Kelly N.; Bayona-Vásquez, Natalia J.; Taylor, Andrew T.; Hilburn, Bryson G.; Freeman, Mary C.; Wares, John P. (Zootaxa, 2025)
We describe as new species Micropterus pucpuggy Freeman & Freeman (Bartram’s Bass), sp. nov., and Micropterus calliurus Freeman & Freeman (Altamaha Bass), sp. nov., which occur allopatrically in four river systems draining the Atlantic Slope of the southeastern United States. In recent decades, biologists and anglers have acknowledged the existence of these two distinctive taxa of black bass, both of which were previously considered synonymous with M. coosae Hubbs & Bailey (Redeye Bass). However, introgression with non-native congeners that have been widely introduced for sport-fishing (including M. henshalli Hubbs & Bailey and M. dolomieu Lacepède) has confounded formal description of M. pucpuggy and M.calliurus. We examined mitochondrial (mtDNA) and nuclear gene sequences of candidate type-specimens of M. pucpuggy and M. calliurus. We then used reduced-representation, short-read sequencing of candidate types along with specimens of six other Micropterus species to identify a series of non-introgressed individuals for each of the two new species. Micropterus pucpuggy and M. calliurus are each reciprocally monophyletic in both mitochondrial and RADseq phylogenies and are diagnosable from all other Micropterus species and from each other in chromatic fin coloration, body pigmentation, and other morphological attributes.